Grooming behavior in goitered gazelles: the programmed versus stimulus-driven hypothesis. Issue 1 (2nd January 2023) - Blank, David A.
Abstract : Self-grooming is the most commonly observed behavior and serves numerous functions, with the removal of ectoparasites likely the most important. According to a predominant conception, grooming is regulated by two mechanisms: a programmed-grooming model and a stimulus-driven model. The programmed-grooming model predicts, first, that smaller body-size females must groom more frequently compared to larger males (body-size principle); second, the smaller young groom significantly more often than adults (developmental grooming); and third, rutting males, busy with social vigilance, groom significantly less often than females (vigilance principle). The impact of molting was also tested on the grooming rate as an additional hypothesis that is not a part of the programmed-grooming model. According to investigations of a wide variety of ungulates in captive and natural conditions, the predictions of the programmed-grooming mechanism were found to be accurate for most sexually dimorphic ungulates. Here, I tested the principles of the programmed-grooming model in free living, wild goitered gazelles ( Gazella subgutturosa ), which are parasitized by both keds and ticks. My study found the following: (a) the body-size principle was not supported by my data, especially during the gazelles' molting and rutting periods; (b) the developmental grooming model did not relate to the grooming behavior of goitered gazelle fawns; (c) the vigilance principle was not applicable to male goitered gazelles; and (d) spring molting increased the grooming rate drastically for both males and females and likely had the greatest effect over any other factor, even though keds also contributed to the grooming rate at this time. Though previous studies of tick parasitism on many ungulate species demonstrated that oral grooming was more consistent with programmed-grooming than the stimulus-driven grooming model, my study of ked parasitism of goitered gazelles showed the opposite, suggesting that grooming driven mechanisms were parasite-host dependent. However, grooming behavior is likely a multifaceted phenomenon depending not only on body size, vigilance rate or even from ectoparasite burden, but also on numerous other factors.